2014
DOI: 10.1128/jvi.03230-13
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Cellular CD4 Exposes HIV-1 Envelope Epitopes Targeted by Antibody-Dependent Cell-Mediated Cytotoxicity

Abstract: Anti-HIV-1 envelope glycoprotein (Env) antibodies without broadly neutralizing activity correlated with protection in the RV144 clinical trial, stimulating interest in other protective mechanisms involving antibodies, such as antibody-dependent cellmediated cytotoxicity (ADCC). Env epitopes targeted by many antibodies effective at mediating ADCC are poorly exposed on the unliganded Env trimer. Here we investigated the mechanism of exposure of ADCC epitopes on Env and showed that binding of Env and CD4 within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

39
600
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 249 publications
(646 citation statements)
references
References 69 publications
39
600
1
Order By: Relevance
“…It has been shown that the replacement of serine 375 by a histidine or tryptophan residue fills the Phe 43 cavity and predisposes Env to assuming a slightly more CD4-bound-like conformation (9). Moreover, it has been shown that sampling of the CD4-bound conformation results in an enhanced exposure of epitopes recognized by anti-cluster A antibodies (14,34). To evaluate whether this enhanced recognition translates into enhanced susceptibility to ADCC, primary CD4 ϩ T cells from healthy HIV-1-negative donors were infected with HIV-1 NL4-3-GFP infectious molecular clones (IMCs) expressing wild-type (WT) strain ADA Env or mutant Env with a histidine (S375H) or a tryptophan (S375W) substitution at position 375.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the replacement of serine 375 by a histidine or tryptophan residue fills the Phe 43 cavity and predisposes Env to assuming a slightly more CD4-bound-like conformation (9). Moreover, it has been shown that sampling of the CD4-bound conformation results in an enhanced exposure of epitopes recognized by anti-cluster A antibodies (14,34). To evaluate whether this enhanced recognition translates into enhanced susceptibility to ADCC, primary CD4 ϩ T cells from healthy HIV-1-negative donors were infected with HIV-1 NL4-3-GFP infectious molecular clones (IMCs) expressing wild-type (WT) strain ADA Env or mutant Env with a histidine (S375H) or a tryptophan (S375W) substitution at position 375.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, primary CD4 ϩ T cells were infected with SHIVs expressing clade C and D HIV-1 Env with the same substitutions in residue 375 (WT and S375H and S375W mutants). Since it is now well established that CD4 present on the cell surface affects Env conformation by forcing it to assume the CD4-bound conformation (13,14,21,22,35), we first evaluated the ability of all the IMCs to downregulate CD4. Figure 2 shows that all IMCs tested, independently of the residue present at position 375, efficiently downregulated CD4 from the cell surface ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations